CTD measurements collected during the first MARUM Waveglider, OpenDAM demo mission - Christoph Waldmann; Sebastian Meckel; Andree Behnken; Robert Huber (PANGAEA, 2019)
CTD data near the ocean surface have been collected by utilizing an autonomous surface vehicle, the Wave Glider® SV3 of Liquid Robotics operated by MARUM. The real-time data coming from the surface drone were transmitted via an Iridium satellite using the OpenDAM module and subsequently reformatted to be directly fed the data into PANGAEA.